Artemis Fowl: The Arctic Incident - Colfer, Eoin.; Parker, Nathaniel (New York, N.Y. : Listening Library, 2004)
When Artemis learns that his father has been kidnapped by the Russian mob, he races to the Arctic Circle to make a daring rescue where he finds an old acquaintance, Captain Holly Short, who is investigating a plot of the goblin mob.
aUnabridged.
aCompact discs.
Read by Nathaniel Parker.
Keywords: Children's audiobooks; Fairies -- Fiction; Magic -- Fiction; Fathers and sons -- Fiction; Organized crime -- Fiction; Audiobooks